Comparing the effectiveness of online and onsite learning in English proficiency classes: Learners’ perspectives - Hung, Luu Nguyen Quoc; Bao, Tran Le Quoc (Journal of Education and e-Learning Research, 2023)
Online education has significantly gained popularity due to new technology and more importantly, the growing impact of the digitalization of the economy. Despite its prominent advantages such as accessibility, affordability and flexibility, the effectiveness of online education is still a constant debate and needs extensive investigations in different research contexts. This study aimed to evaluate the effectiveness of online learning in comparison to traditional learning in the context of English language teaching. This descriptive study was undertaken with learners of English as a foreign language (EFL) in English proficiency preparation classes, employing an online questionnaire together with final scores of proficiency tests. The results revealed that the participants had relatively positive perceptions towards online learning in all four aspects: course content, teachers, learning environment and course supports. The significant finding was that when comparing the final results of the VSTEP exams, the online learners generally were able to perform better than the learners in traditional classrooms, though the difference was not largely remarkable. Online education in the new normal will continue to excel and the effectiveness of this learning mode certainly needs further investigation from different perspectives.